If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 * 15X + 15 = X Multiply 27 * 15 405X + 15 = X Reorder the terms: 15 + 405X = X Solving 15 + 405X = X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 15 + 405X + -1X = X + -1X Combine like terms: 405X + -1X = 404X 15 + 404X = X + -1X Combine like terms: X + -1X = 0 15 + 404X = 0 Add '-15' to each side of the equation. 15 + -15 + 404X = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 404X = 0 + -15 404X = 0 + -15 Combine like terms: 0 + -15 = -15 404X = -15 Divide each side by '404'. X = -0.03712871287 Simplifying X = -0.03712871287
| (3x-10)*2=x | | 4x-5+2(3x)+17=-2-5x+3 | | 3=9x+2+x | | 27*15+15=X | | c=9x+b+x | | (3/2)F=67/4 | | 4/10=5x | | 5x+8=x-2 | | 27.15+15=X | | 6x+3-7x=6 | | y/-2=11 | | -3(3p+3)-2(3-14p)=3(9+6p) | | tan^2(x)-1/343 | | 13-16=5y+6-4y | | -6x+3(-x+14)=141 | | 12x+2=4x-6 | | 4(x+1.2)=3x+9.7 | | 175=7(-5x-5) | | 122=69xT | | 10log(30/10^-12) | | 1-1/64x^4=0 | | 1-1/64x^4 | | -2x+4a=6 | | (-19)(7/11) | | 3(2x-1)+2=19 | | 29+34-28+(36-2)= | | 5x-7x-9x=-19 | | 3/2b-1/3 | | w=2.5+15t | | bg-5=1243 | | x+(x*.22)=583 | | (3x-7x-6)+(-3x+2)= |